(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2019)
PCR is a powerful tool for the amplification of genetic sequences but sometimes, even though using an established PCR protocol that had been optimized and successful for the amplification of a particular DNA segment, use of that same protocol on a different region can result in a less than desirable outcome. Therefore, an experiment was conducted at Molecular biology laboratory of Malaysian Nuclear Agency during December 2016 to January 2017 used seeds of 6 indica rice cultivars. To conduce RAPD experiments for the rice species it was established the following reaction conditions for the final volume of 20 μl where 0.1 unit of Taq DNA polymerase, 0.4 μl of each dNTP, 2.5 mM MgCl2, 1 μl primer and 2.0 μl of DNA template. From this experiment, it is clear that after mutation the parent MR219 performed some genetic modification and produce genetically different variety namely NMR151, NMR152, ML3, ML10 and ML30. These mutant varieties have two different groups based on their mutation source and it is clear enough from their RAPD profile. Int. J. Agril. Res. Innov. & Tech. 9 (1): 1-7, June, 2019